Visiting crowded places during the COVID-19 pandemic. A panel study among adult Norwegians - Aarø, Leif Edvard; Veneti, Lamprini; Vedaa, Øystein; Smith, Otto R. F.; De Blasio, Birgitte Freiesleben; Robberstad, Bjarne (Frontiers in Public Health, 2022)
Non-pharmaceutical interventions, including promotion of social distancing, have been applied extensively in managing the COVID-19 pandemic. Understanding cognitive and psychological factors regulating precautionary behavior is important for future management. The present study examines the importance of selected factors as predictors of having visited or intended to visit crowded places. Six online questionnaire-based waves of data collection were conducted in April–October 2020 in a Norwegian panel (≥18 years). Sample size at Wave 1 was 1,400. In the present study, “Visited or intended to visit crowded places” for different types of locations were the dependent variables. Predictors included the following categories of items: Perceived response effectiveness, Self-efficacy, Vulnerability, Facilitating factors and Barriers. Data were analyzed with frequency and percentage distributions, descriptives, correlations, principal components analysis, negative binomial-, binary logistic-, and multiple linear regression, and cross-lagged panel models. Analyses of dimensionality revealed that a distinction had to be made between Grocery stores, a location visited by most, and locations visited by few (e.g., “Pub,” “Restaurants,” “Sports event”). We merged the latter set of variables into a countscore denoted as “Crowded places.” On the predictor side, 25 items were reduced to eight meanscores. Analyses of data from Wave 1 revealed a rather strong prediction of “Crowded places” and weaker associations with “Supermarket or other store for food.” Across waves, in multiple negative binomial regression models, three meanscore predictors turned out to be consistently associated with “Crowded places.” These include “Response effectiveness of individual action,” “Self-efficacy with regard to avoiding people,” and “Barriers.” In a prospective cross-lagged model, a combined Response effectiveness and Self-efficacy score (Cognition) predicted behavior (“Visited or intended to visit crowded places”) prospectively and vice versa. The results of this study suggest some potential to reduce people's visits to crowded locations during the pandemic through health education and behavior change approaches that focus on strengthening individuals' perceived response effectiveness and self-efficacy.